Far‐Red/Near‐Infrared Emissive (1, 3‐Dimethyl)barbituric Acid‐Based AIEgens for High‐Contrast Detection of Metastatic Tumors in the Lung. Issue 6 (28th December 2018) - Gao, Heqi; Bao, Pingping; Dai, Shuxin; Liu, Ruihua; Ji, Shenglu; Zeng, Sheng; Shen, Jing; Liu, Qian; Ding, Dan
Abstract: Despite of the enthusiastic research in aggregation‐induced emission luminogens (AIEgens) in recent years, the ones that can be smoothly used for sophisticated biomedical applications such as in vivo bioimaging of pulmonary metastatic tumors during surgery are still limited. Herein, we report the design and synthesis of a new series of far‐red/near‐infrared (FR/NIR) fluorescent AIEgens that consist of methoxy‐substituted tetraphenylethene (TPE) as the electron‐donating moiety, (1, 3‐dimethyl)barbituric acid as the electron‐withdrawing moiety, and different π‐bridge units. As compared to benzene or 3, 4‐ethylenedioxythiophene, using thiophene as the π‐conjugation unit between the donor and acceptor results in a relatively higher absolute fluorescence quantum yield (14.5 %) in water when formulating the corresponding AIEgens into nanoparticles (AIE dots) with an amphiphilic co‐polymer as the doping matrix. The highly FR/NIR‐emissive thiophene‐based AIE dots are demonstrated to be potent for intraoperative detection of pulmonary metastatic tumors, particularly the micro‐sized ones, with excellent signal‐to‐background ratio. Abstract : Seeing red : Far‐red/near‐infrared fluorescent (1, 3‐dimethyl)barbituric acid‐based AIE dots have been developed, which give excellent performance in intraoperative diagnosis of pulmonary metastatic tumors in a high‐contrast manner.